Enhancing short-packet communications: BLER performance in RIS-assisted ambient backscatter NOMA systems - Le Si Phu; Tan N. Nguyen; Bui Vu Minh; Phu Tran Tin; Miroslav Voznak (PLoS ONE, 2025)
Short-packet communication (SPC) is a key enabler for ultra-reliable low-latency communication (URLLC) in next-generation wireless networks. In this paper, we investigate the block error rate (BLER) performance of a reconfigurable intelligent surface (RIS)-assisted ambient backscatter communication (AmBC) system operating under a non-orthogonal multiple access (NOMA) framework. Different from existing works, our study considers a Nakagami-m fading environment and derives closed-form expressions for the average and asymptotic BLER. By leveraging power-domain NOMA and RIS-assisted reflection, we optimize signal reception for both direct and backscattered links, enhancing spectral efficiency and communication reliability. Numerical and Monte Carlo simulation results validate our analytical findings, demonstrating significant performance gains in terms of BLER reduction and system throughput improvement. These results highlight the potential of RIS-assisted AmBC-NOMA systems in enabling efficient SPC for URLLC applications.